Observer's guide to star clusters - Inglis, Mike (The Patrick Moore Practical Astronomy Series, 2013)
This book is for amateur astronomers of all expertise, from beginner to experienced. It is intended to be used at the telescope - small, medium, or large - or even by an observer using binoculars or the naked eye. It is organized by constellation and will enable practical observers to locate the approximate positions of important star clusters in the 88 constellations from literally anywhere on Earth.  In practice, GO-TO telescopes can usually locate clusters accurately enough, but this, of course, first requires that the observer knows what is visible in the sky at a given time and from a given location, so as to input a locatable object! This is where the book becomes an essential aid to finding star clusters to observe. Observers who do not have computer-controlled telescopes can of course use the traditional "star-hopping" method to find specific objects, starting from the given reference stars.  The constellation maps in this book are in black and white, so that they can be read by the light of a red LED observer's reading light. The clusters and their names/numbers are printed in bold black, against a "grayed-out" background of stars and constellation figures.  Used as a self-contained reference, Observer's Guide to Star Clusters offers detailed and up-to-date coverage of these beautiful objects. This book will soon become an essential piece of equipment for you, as essential as your telescope!